Water Quality Monitoring System for Catfish Using IoT - Murugu, Karthigeyen; Nor'aisah Sudin, (Evolution in Electrical and Electronic Engineering, 2024)
This work introduces a water quality monitoring system that was made for catfish ponds, using the capabilities of the Internet of Things (IoT). The system integrates three essential sensors which are pH sensor, temperature sensor, and ultrasonic sensor to monitor the aquatic environment. The pH sensor continuously measures acidity levels, crucial for maintaining optimal conditions for catfish health. Simultaneously, the temperature sensor captures real-time temperature data, offering insights into the thermal dynamics of the pond. The ultrasonic sensor, strategically placed at the water surface, enables to recording of water level measurement, contributing to the assessment of water volume and environmental variations. The output readings can be seen on the LCD. Other than that, wireless communication channels transmit sensor data to the Blynk IoT platform, establishing a seamless connection for remote monitoring. The Blynk mobile application serves as an intuitive interface, allowing users to visualize real-time data and receive notifications directly on their devices. If the quality of the water in the pond is in bad condition, it will alert the farmer in the Blynk app. For example, if the temperature, pH level, and water level are not in a normal state it will alert the farmer by giving a notification on the app. For temperature, the ideal is between 26 to 32 Celsius, for the pH level the water should be between 5.5 to 7.5, and the ideal water level range for the catfish not to jump out from the water is around 1 foot which equals 30cm to 40cm. This water quality monitoring system represents a significant advancement in aquaculture management, empowering catfish farmers with timely and actionable insights. The study evaluates the system's effectiveness in providing accurate data and notifications through the Blynk app, offering a promising solution for sustainable catfish farming and contributing to broader initiatives addressing water quality challenges in aquaculture.